Catalyst and preparation method thereof, and carbon nanotube and preparation method thereof

By using modified blast furnace slag as the carbon nanotube catalyst support, the problems of high cost and singularity of the carrier material are solved, and high-efficiency preparation of high-quality carbon nanotubes is achieved, reducing production costs and broadening the window for reaction activity temperature.

CN119259058AActive Publication Date: 2025-01-07ZHEJIANG FANGTAISIKE TECHNOLOGY CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411796521.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-01-07
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The high cost and singularity of existing carbon nanotube catalyst support materials limits their application potential in catalytic cracking reactions, resulting in increased production complexity and cost.

Method used

Blast furnace slag is used as a multi-component composite carrier, and is modified by metal oxide particles to improve its specific surface area and reactivity, and form crystalline phases with multiple crystal structures to inhibit the growth and migration of active metals, fix the active metal particles, and reduce the Carbon deposits form.

Benefits of technology

It significantly reduces the cost of catalyst raw materials, improves the yield and stability of carbon nanotubes, produces high-quality carbon nanotubes with consistent pipe diameters and high yields, broadens the window of reaction activity temperature, and enhances the adsorption and reaction activity of the carrier.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259058A_ABST
    Figure CN119259058A_ABST
Patent Text Reader

Abstract

The present invention discloses a catalyst for synthesizing carbon nanotubes, the catalyst comprising: a body comprising a plurality of catalytic metal particles; the carrier comprises a plurality of carrier particles, the carrier particles are of a porous structure, the specific surface area of the carrier particles is larger than that of the catalytic metal particles, the catalytic metal particles are loaded by the carrier particles, and the material of the carrier particles comprises blast furnace slag; and a modifier comprising a plurality of metal oxide particles. The invention also discloses a preparation method of the catalyst, a carbon nanotube and a preparation method of the carbon nanotube.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of carbon nanotubes, and in particular to a catalyst and a preparation method thereof, and a carbon nanotube and a preparation method thereof. Background Art

[0002] The existing technology mainly uses supported catalysts for the synthesis and preparation of carbon nanotubes. The catalyst is composed of active metals, additives and carriers. The selection of carrier materials is the main source of preparation costs. However, the current carrier raw materials are usually selected from oxides such as Al2O3, MgO, SiO2 and CaO and their salt compounds. Although the above selections show good stability, the cost of raw materials is relatively high. In addition, the singleness of these carrier materials limits their application potential in catalytic cracking reactions. In order to achieve the best catalytic effect, it is often necessary to mix a variety of salts through complex ratios and adjustments to find the optimal combination, which undoubtedly increases the complexity and cost of preparation.

[0003] Therefore, finding low-cost and high-performance carrier materials plays a decisive role in reducing the overall cost of catalysts. How to adjust the catalyst formula economically and efficiently to significantly increase production and performance while reducing costs has become a difficult problem that needs to be solved urgently. Summary of the invention

[0004] The present invention aims to solve one of the technical problems in the related art to a certain extent. To this end, the present invention provides a catalyst and a preparation method thereof and a carbon nanotube and a preparation method thereof.

[0005] In order to achieve the above object, as a first aspect of the present invention, a catalyst is disclosed, which is used for synthesizing carbon nanotubes, and the catalyst comprises: a body comprising a plurality of catalytic metal particles; A carrier, the carrier comprising a plurality of carrier particles, wherein the specific surface area of ​​the carrier particles is greater than the specific surface area of ​​the catalytic metal particles, the catalytic metal particles are supported by the carrier particles, and the material of the carrier particles comprises blast furnace slag; A modifier comprises a plurality of metal oxide particles and is used for modifying the carrier particles.

[0006] Furthermore, a plurality of the metal oxide particles are distributed inside and / or on the surface of the carrier particles, and the plurality of the metal oxide particles are combined with the carrier particles.

[0007] Furthermore, the modifier includes a basic metal oxide.

[0008] Furthermore, the modifier includes at least one of magnesium oxide, zinc oxide, zirconium oxide and titanium oxide.

[0009] Furthermore, in the catalyst, the modifier accounts for between 0.5% and 15% of the weight of the carrier.

[0010] Furthermore, in the catalyst, the mass of the metal element in the main body is 10% to 30% of the weight of the carrier. Furthermore, the metal element of the catalytic metal particles includes at least one of iron, cobalt and nickel.

[0011] As a second aspect of the present invention, a method for preparing a catalyst is provided, the preparation method comprising: Providing initial blast furnace slag; Enriching catalytic metals and modifying metals in the initial blast furnace slag to obtain an initial catalyst; The initial catalyst is calcined to prepare the above catalyst, which is used to synthesize carbon nanotubes.

[0012] Further, the catalytic metal and the modifying metal are enriched in the initial blast furnace slag to obtain the initial catalyst, comprising: Mixing a first metal salt, a second metal salt and water to form a mixed solution, wherein the metal in the first metal salt corresponds to the catalytic metal, and the metal in the second metal salt corresponds to the modified metal; The mixed solution is mixed with the initial blast furnace slag by an impregnation method or a co-precipitation method to obtain a first mixed solution; The first mixed liquid is dried and crushed to obtain the initial catalyst.

[0013] Furthermore, in the step of calcining the initial catalyst, the calcination temperature is between 300° C. and 700° C., and the calcination time is between 0.5 hours and 3 hours.

[0014] Further, providing initial blast furnace slag includes: crushing the blast furnace slag to obtain first blast furnace slag; The first blast furnace slag is subjected to an acid modification treatment using an acid solution, wherein the acid solution corrodes the first blast furnace slag to form a surface microporous structure, thereby obtaining the initial blast furnace slag.

[0015] As a third aspect of the present invention, a method for preparing carbon nanotubes is disclosed, the method comprising: heating a catalyst to between 680°C and 800°C, introducing a carbon source gas for reaction, and obtaining initial carbon nanotubes, wherein the catalyst is the above-mentioned catalyst; The initial carbon nanotubes are cooled to room temperature to obtain the carbon nanotubes.

[0016] As a fourth aspect of the present invention, a carbon nanotube is disclosed. The carbon nanotube is prepared by the above-mentioned preparation method.

[0017] The present invention is aimed at the byproduct of blast furnace slag unique to my country, which not only becomes an environmental burden but also causes great waste of resources due to its large accumulation. In view of the fact that blast furnace slag is rich in key components such as CaO, SiO2, Al2O3, MgO, etc., it can be regarded as a multi-component composite carrier, and its stable chemical composition and suitable component ratio make it an ideal choice for catalyst carrier. By applying blast furnace slag to the field of carbon nanotube preparation, not only the raw material cost of the catalyst is greatly reduced, but also the resource utilization of blast furnace slag is realized, which effectively promotes the development of resource recycling economy.

[0018] Compared with traditional catalyst carriers for carbon nanotubes, blast furnace slag has similar physical and chemical properties, including excellent adsorption performance, outstanding thermal stability and chemical stability. However, as a multi-component composite carrier, blast furnace slag has higher adsorption performance and reaction activity. At the same time, the multi-component composite carrier can broaden the reaction activity temperature window, and a variety of crystal phases with crystal structures are formed inside the multi-component composite carrier. There are lattice distortions between these polycrystalline phases, which hinders the further growth of active metals during high-temperature catalysis, thereby effectively inhibiting the increase in the diameter of carbon nanotubes, and also making it difficult for active components to migrate and aggregate to improve the activity of the catalyst and increase the yield. These characteristics make the catalyst with blast furnace slag as the carrier show stronger stability in the preparation of carbon nanotubes, which helps to produce high-quality carbon nanotubes with consistent diameter and higher yield.

[0019] In view of the problems of insufficient porosity, limited specific surface area and influence on active component loading and dispersion when blast furnace slag is used as a catalyst carrier, the present invention also specially adopts metal oxide particles as a modifier to modify blast furnace slag. On the one hand, metal oxide can improve the inherent acidity of blast furnace slag, reduce the carbon deposition of subsequent carbon source on the surface of active metal particles, or reduce carbon deposition by providing alkaline sites; on the other hand, metal oxide can interact with slag carrier, so that the original crystal phase structure of blast furnace slag is destroyed, micropores are generated on the surface of the carrier and the internal channels are opened, providing active sites for active metal particles and reaction gases, and the lattice distortion generated by the destruction can also inhibit the growth and migration of active metal particles. At the same time, the metal oxide modifier not only enhances the adsorption capacity of blast furnace slag carrier, but also has a certain adsorption capacity. The two cooperate to adsorb active metal particles, so that active metal particles are fixed on the carrier, further reducing the detachment and desorption of active metal particles.

[0020] These effective modification methods significantly optimize the performance of blast furnace slag as a catalyst carrier, providing a solid guarantee for the preparation of carbon nanotubes with even better performance.

[0021] These features and advantages of the present invention will be disclosed in detail in the following specific embodiments and drawings. The best embodiments or means of the present invention will be described in detail in conjunction with the drawings, but they are not intended to limit the technical solutions of the present invention. In addition, there are multiple features, elements, and components that appear in each of the following texts and drawings, and different symbols or numbers are marked for convenience, but they all represent components with the same or similar structures or functions. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The present invention will be further described below in conjunction with the accompanying drawings: Figure 1 A schematic structural diagram of an embodiment of the catalyst provided by the present invention; Figure 2 A flow chart of an embodiment of the catalyst preparation method provided by the present invention; Figure 3 This is a scanning electron microscope photo of carbon nanotubes prepared by the catalyst of Example 1; Figure 4 This is a scanning electron microscope photograph of carbon nanotubes prepared by the catalyst of Example 3; Figure 5 This is a scanning electron microscope photograph of carbon nanotubes prepared using the catalyst of Comparative Example 1; Figure 6 This is a scanning electron microscope photograph of carbon nanotubes prepared using the catalyst of Comparative Example 3.

[0023] Description of Reference Numerals 1: Catalyst; 1a: Catalytic metal particles; 1b: Carrier particles; 1c: Metal oxide particles DETAILED DESCRIPTION Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments in the implementation manner are intended to be used to explain the present invention and should not be construed as limiting the present invention.

[0024] References to "one embodiment" or "example" or "example" in this specification mean that a particular feature, structure, or characteristic described in conjunction with the embodiment itself may be included in at least one embodiment disclosed herein. The appearance of the phrase "in one embodiment" in various places in the specification does not necessarily refer to the same embodiment.

[0025] The shapes, sizes, proportions, angles, quantities, etc. disclosed in the drawings used to explain the catalyst and carbon nanotubes of the present invention are exemplary, and the present invention is not limited to the contents shown. For example, although the carrier particles are represented by round particles in the drawings, it does not mean that the actual carrier particles are a combination of round particles, and the size, position, structure, etc. of the different round particles shown in the drawings are intended to explain the present invention, and the present invention is not necessarily limited to the above parameters shown.

[0026] Carbon nanotubes, as a unique one-dimensional nanomaterial, have shown broad application potential in many fields due to their excellent mechanical properties, electrical properties, thermal properties, chemical stability and light weight. They are widely used to improve the performance of lithium-ion batteries, enhance the performance of conductive plastics, serve as a reinforcing agent for high-performance composite materials, and play an important role in biomedical research, environmental protection and sensor technology. Among them, the lithium-ion battery field is the main market for large-scale commercial applications of carbon nanotubes. With the advancement of technology and the expansion of application fields, the application prospects of carbon nanotubes will continue to expand.

[0027] The cost issue is one of the key factors restricting the widespread application of carbon nanotubes. By developing new catalysts, reducing the cost of raw materials of catalysts, and improving product performance at the same time, the production cost can be reduced and the market competitiveness of products can be improved. Catalysts are composed of active metals, additives and carriers. Among them, the carrier often occupies more than half of the total mass of the catalyst. Therefore, finding a carrier material with low cost and excellent performance plays a decisive role in reducing the overall cost of the catalyst. At present, the carrier usually uses oxides such as Al2O3, MgO, SiO2 and CaO. The widely used carrier raw materials, such as high-purity aluminum salts, magnesium salts and their oxides, show good stability, but the raw material cost is relatively high. In addition, in order to achieve the best catalytic effect, it is often necessary to mix a variety of salts through complex ratios and adjustments to find the optimal combination, which undoubtedly increases the complexity and cost of preparation.

[0028] The inventors of the present application have found that blast furnace slag, as a by-product of the steel smelting process, is not only a burden on the environment, but also a huge waste of resources. The slag components come from the following aspects: (1) gangue in the ore; (2) coke ash; (3) flux oxides. The main components of gangue and ash are acidic oxides of SiO2 and Al2O3; the flux oxides are mainly alkaline oxides of CaO and MgO, and these components account for up to 95% of the total mass. These components usually have excellent adsorption properties provided by the porous structure, as well as excellent chemical stability and thermal stability. They have physical and chemical properties similar to those of traditional carbon nanotube catalyst carriers, and are an ideal choice as a carrier. Using blast furnace slag as a carrier greatly reduces the raw material cost of the catalyst, and realizes the resource utilization of blast furnace slag, which effectively promotes the development of resource recycling economy.

[0029] At the same time, blast furnace slag can be regarded as a multi-component composite carrier composed of components such as CaO-SiO2-MgO-Al2O3. The synergistic effect of its multiple components can promote a more uniform dispersion of active components on the carrier surface, and the multiple components can broaden the reaction activity temperature range, which makes the catalyst with blast furnace slag as the carrier show stronger stability in the preparation of carbon nanotubes, which in turn helps to produce high-quality carbon nanotubes with consistent diameter and higher yield.

[0030] However, when blast furnace slag is used as a catalyst carrier, there may be problems such as insufficient porosity, limited specific surface area, and influence on the loading and dispersion of active components. Based on the above problems, as a first aspect of the present invention, a catalyst is disclosed, such as Figure 1 As shown, the catalyst 1 is used to synthesize carbon nanotubes, and the catalyst 1 comprises: A main body, the main body comprising a plurality of catalytic metal particles 1a; A carrier, the carrier comprises a plurality of carrier particles 1b, wherein the specific surface area of ​​the carrier particles is greater than the specific surface area of ​​the catalytic metal particles, the catalytic metal particles are supported by the carrier particles, and the material of the carrier particles comprises blast furnace slag; The modifier includes a plurality of metal oxide particles 1c.

[0031] Compared with traditional catalyst carriers for carbon nanotubes, blast furnace slag is a multi-component composite carrier with higher adsorption performance and reaction activity. At the same time, the multi-component composite carrier can broaden the reaction activity temperature window, and a variety of crystalline phases with crystal structures are formed inside the multi-component composite carrier. There is lattice distortion between these polycrystalline phases, which hinders the further growth of active metals during high-temperature catalysis, thereby effectively inhibiting the increase in the diameter of carbon nanotubes, and making it difficult for active components to migrate and aggregate to improve the activity of the catalyst and increase the yield. These characteristics make the catalyst with blast furnace slag as the carrier show stronger stability in the preparation of carbon nanotubes, which in turn helps to produce high-quality carbon nanotubes with consistent diameter and higher yield.

[0032] The present invention does not impose any particular limitation on the method for obtaining the blast furnace slag, which can be purchased or prepared.

[0033] In the present invention, the modifier is used to modify the carrier particles 1b of blast furnace slag, and metal oxide particles 1c are used as the modifier. On the one hand, the metal oxide particles 1c can improve the inherent acidity of blast furnace slag, reduce the carbon deposition of subsequent carbon sources on the surface of catalytic metal particles 1a, or reduce carbon deposition by providing alkaline sites; on the other hand, the structure of blast furnace slag is more compact after high temperature treatment, and the specific surface area and pore volume are relatively small, and the metal oxide particles 1c can interact with the slag carrier or form a solid solution, so that the original crystal phase structure of blast furnace slag is destroyed, micropores are generated on the surface of the carrier and the internal channels are opened, providing active sites for catalytic metal particles 1a and reaction gases, and the lattice distortion generated by the destruction can also inhibit the growth and migration of catalytic metal particles 1a. At the same time, the metal oxide particles 1c not only enhance the adsorption capacity of the blast furnace slag carrier, but also have a certain adsorption capacity. The two cooperate to adsorb the catalytic metal particles 1a, so that the catalytic metal particles 1a are fixed on the carrier particles 1b, further reducing the detachment and desorption of the catalytic metal particles 1a.

[0034] The modifier of the present invention significantly optimizes the performance of blast furnace slag as a catalyst carrier by modifying blast furnace slag, and provides a solid guarantee for preparing carbon nanotubes with more excellent performance.

[0035] The present invention does not impose any special restrictions on the distribution of the modifier in the catalyst. In order to improve the modification effect and make the interaction between the metal oxide particles 1c and the carrier particles 1b stronger, thereby obtaining higher adsorption performance and reaction activity, preferably, a plurality of metal oxide particles 1c are distributed inside and / or on the surface of the carrier particles 1b. This distribution method allows a single carrier particle 1b to be simultaneously subjected to the interaction of the metal oxide particles 1c at multiple positions, and multiple positions can produce lattice distortion or changes in crystal phase, thereby effectively dispersing more catalytic metal particles 1a and inhibiting their growth. In some embodiments, the metal oxide particles 1c can be adsorbed into the porous structure of the carrier particles 1b. In the subsequent high-temperature process, the adsorbed multiple metal oxide particles 1c It combines with the carrier particles 1b by physical or chemical reaction. For example, the modifier is Al2O3, which is adsorbed in the pores of the blast furnace slag carrier particles in the form of Al2O3 particles. In the slag, Al2O3 is a weakly acidic oxide. As a network former in the slag, it is easy to combine with TiO2, MgO, SiO2 and other substances in the blast furnace slag to form a composite crystal structure. The lattice distortion caused by this crystal structure change will hinder the growth and migration and aggregation of catalytic metal particles, thereby improving the dispersion of the carrier, and alumina itself also has a porous adsorption effect, which further increases the adsorption capacity of the carrier for catalytic metal particles. In addition, different metal oxide particles can be added to adjust the phase transition nodes of the multi-components to obtain an ideal phase structure composition and improve the comprehensive performance of the carrier.

[0036] The present invention does not specifically limit the composition of the modifier, and only needs to satisfy that the metal oxide particles can achieve the modification of blast furnace slag. For example, the modifier adopts at least one of MgO, Al2O3, ZnO, ZrO2 and TiO2. Preferably, the modifier adopts alkaline metal oxide, which has the advantages of neutralizing the acidity of the blast furnace slag carrier to avoid the carbon deposition effect on the one hand, and the alkaline metal oxide particles can provide electrons to the catalytic metal particles, so that the d band center of the catalytic metal atom moves up and gradually approaches the Fermi level, increasing the stability of the bonding, so that the adsorption strength of the catalytic metal atom is improved, and the absorption and dissociation of the carbon source on the surface of the catalytic metal atom are promoted, providing more activity for the catalytic metal atom. Preferably, the modifier includes at least one of magnesium oxide, zinc oxide, zirconium oxide and titanium oxide. The above-mentioned alkaline metal oxide reacts with the acidic blast furnace slag carrier to form channels on the surface and inside of the carrier particles, which can provide a larger adsorption area for the active substance.

[0037] The present invention does not make any special restrictions on the weight ratio of the modifier to the carrier. A lower weight ratio will significantly reduce the modification effect and fail to effectively improve the various properties of the blast furnace slag carrier. A higher weight ratio will lead to a decrease in the quality of the generated carbon nanotubes. After the modifier accounts for more than 50%, the diameter of the generated carbon nanotubes becomes thicker and the carbon yield decreases. In addition, too much modifier will coat the surface of the blast furnace slag, which may block the microporous structure and affect the catalytic metal particles from entering the carrier. At the same time, the blast furnace slag carrier properties tend to be a single carrier, and lattice distortion cannot be generated, thereby failing to inhibit the growth or migration of the catalytic metal particles. Preferably, in the catalyst, the modifier accounts for between 0.5% and 15% of the weight of the carrier.

[0038] The present invention does not impose any special restrictions on the weight ratio of the catalytic metal particles in the carrier. The lower the weight ratio of the catalytic metal particles to the carrier, that is, the lower the loading amount, the more uniform the dispersion of the catalytic metal particles on the carrier, the smaller the catalytic metal particles, the finer the diameter of the prepared carbon nanotubes, and the larger the specific surface area of ​​the carbon nanotubes. However, too high a loading amount may introduce more impurities. Preferably, in the catalyst, the mass of the metal element in the main body is 10% to 30% of the weight of the carrier.

[0039] The present invention does not specifically limit the catalytic metal particles. Preferably, the catalytic metal particles contain at least one of iron, cobalt, nickel and molybdenum. Iron, cobalt and nickel can react with carbon sources to form metastable carbides, so that the catalysts produced by them have the highest efficiency in growing carbon nanotubes, and are ideal choices for catalysts for synthesizing carbon nanotubes.

[0040] As a second aspect of the present invention, a method for preparing a catalyst is provided, such as Figure 2 As shown, the preparation method comprises: Step S100, providing initial blast furnace slag; Step S110, enriching catalytic metal and modifying metal in initial blast furnace slag to obtain an initial catalyst, wherein the modifying agent includes a metal oxide; Step S120, calcining the initial catalyst to prepare the above-mentioned catalyst, which is used to synthesize carbon nanotubes.

[0041] In step S100, the initial blast furnace slag includes components such as CaO, SiO2, Al2O3, and MgO. In order to improve the surface area, pore volume, adsorption, etc. of the initial blast furnace slag as a carrier, some physical and chemical modifications are performed on the initial blast furnace slag, specifically including: The blast furnace slag is crushed to obtain the first blast furnace slag. As an optional implementation method, the blast furnace slag is crushed by high-speed shear crushing technology, and the first blast furnace slag below 100 mesh is obtained by screening. Crushing the blast furnace slag can promote the subsequent catalytic metal and modifier to be fully mixed with it, thereby increasing the reaction area.

[0042] The first blast furnace slag is subjected to acid modification treatment using an acidic solution, wherein the acidic solution corrodes the first blast furnace slag to form a surface microporous structure to obtain initial blast furnace slag. Preferably, the acid used to modify the blast furnace slag can be at least one of nitric acid, hydrochloric acid and citric acid.

[0043] In step S110, the catalytic metal and the modified metal are enriched in the initial blast furnace slag to obtain the initial catalyst, which includes: Mixing a first metal salt and a second metal salt with water to form a mixed solution, wherein the metal in the first metal salt corresponds to a catalytic metal, and the metal in the second metal salt corresponds to a modified metal. Specifically, the first metal salt includes any one or more of an iron salt, a cobalt salt, a nickel salt, and a molybdenum salt, and the salt includes at least one of a nitrate, a hydrochloride, an acetate, and a sulfate. The molybdenum salt is ammonium heptamolybdate, and the second metal salt includes at least one of a magnesium salt, an aluminum salt, a zinc salt, a zirconium salt, and a titanium salt. Weigh a set amount of the first metal salt and the second metal salt and dissolve them in deionized water. Preferably, the concentration of the mixed salt is between 0.5 mol / L and 5 mol / L. The mixed solution is mixed with the initial blast furnace slag by an impregnation method or a coprecipitation method to obtain a first mixed solution. In some embodiments, the step of the impregnation method includes: adding the initial blast furnace slag to the above mixed solution, stirring at high speed for 6 hours at room temperature, then heating to 80 ° C and continuing to stir until the water is completely evaporated. In other embodiments, the step of the coprecipitation method includes: adding the initial blast furnace slag to the above mixed solution, stirring at high speed for 30 minutes at room temperature to form a suspension. Under continuous high-speed stirring, the precipitant is slowly added to the suspension until the pH value of the mixed solution reaches a range of 9 to 11. Then, it is allowed to stand for 3 hours and washed to neutrality by a centrifuge. Preferably, the precipitant is selected from at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate and ammonia water. The concentration of the precipitant is between 0.5 mol / L and 5 mol / L, and the drop rate of the precipitant is between 1 mL / min and 10 mL / min to obtain a better precipitation effect.

[0044] The first mixed liquid is dried and crushed to obtain an initial catalyst. In order to fully remove moisture and reduce the particle size of the catalyst, preferably, the drying temperature is in the range of 60°C to 120°C, and a high-speed shear crushing method is used to crush the dried solid matter to an average particle size of less than or equal to 5 microns.

[0045] In step S120, preferably, the calcination temperature is between 300°C and 700°C, the calcination time is between 0.5 hours and 3 hours, and the calcination atmosphere is air.

[0046] As a third aspect of the present invention, a method for preparing carbon nanotubes is disclosed, the method comprising: heating the above-mentioned catalyst to between 680° C. and 800° C., introducing a carbon source gas for reaction, and obtaining initial carbon nanotubes; in some embodiments, in a horizontal fixed bed reactor, the catalyst powder is evenly spread in a quartz boat, and under nitrogen protection, the temperature is gradually raised to between 680° C. and 800° C., at least one of methane, ethylene and propylene gas is introduced as a carbon source, and after the reaction reaches a set time, the gas supply is turned off; The initial carbon nanotubes are cooled to room temperature to obtain carbon nanotubes, and the cooling atmosphere is nitrogen.

[0047] As a fourth aspect of the present invention, a carbon nanotube is disclosed. The carbon nanotube is prepared by the above-mentioned preparation method.

[0048] The present invention will be further described below in conjunction with preparation examples and embodiments.

[0049] Preparation Example Preparation Example 1 A method for preparing a catalyst, comprising: S1. providing initial blast furnace slag, wherein the blast furnace slag is crushed by high-speed shear crushing technology and sieved to obtain slag with a mesh size of less than 100; S2. Enriching the catalytic metal and the modified metal in the initial blast furnace slag. Specifically, weighing 7.2 g of ferric nitrate and 4.9 g of cobalt nitrate, dissolving them in 35 mL of deionized water to form a mixed solution with a concentration of 1 mol / L, weighing 10 g of the initial blast furnace slag and mixing it with the mixed solution, stirring at high speed at room temperature for 6 h, then heating to 80 ° C and continuing to stir until the water is completely evaporated, transferring the solid material obtained above to a 100 ° C oven and drying it for 12 h. After drying, crushing it to obtain an initial catalyst; S3. The initial catalyst is calcined. Specifically, the initial catalyst is placed in a muffle furnace and calcined at 600° C. in an air atmosphere for 0.5 h to obtain a Fe-Co / BFS catalyst (the blast furnace slag is referred to as BFS).

[0050] Preparation Example 2 The catalyst was prepared by the same preparation method as in Preparation Example 1, except that in step S1, the blast furnace slag was crushed to obtain the first blast furnace slag, 20 g of the first blast furnace slag was weighed and mixed with 30 mL of nitric acid (concentration of 1 mol / L), soaked for 3 h, and then filtered and washed with deionized water until the pH value of the mixture reached 7. After that, the filter cake was placed in an oven at 120°C and dried for about 12 hours, and finally, calcined in air at 450°C for 1 hour. Finally, the Fe-Co / hn-BFS catalyst was prepared (the nitric acid-modified blast furnace slag was recorded as hn-BFS).

[0051] Preparation Example 3 The catalyst was prepared by the same preparation method as in Preparation Example 1, except that, in step S2, 7.2 g of ferric nitrate, 4.9 g of cobalt nitrate and 3.2 g of magnesium nitrate were weighed and dissolved in 47 mL of deionized water to form a mixed solution with a concentration of 1 mol / L, 10 g of initial blast furnace slag was weighed and mixed with the mixed solution, and stirred at high speed for 30 min at room temperature to form a suspension. Under continuous high-speed stirring, a sodium hydroxide solution with a concentration of 2 mol / L was added dropwise to the suspension at a rate of 1 mL / min until the pH value of the mixed solution reached a range of 9 to 11. Then, it was allowed to stand for 3 h and washed to neutrality by a centrifuge. The above precipitate was transferred to an 80 °C oven and dried for 12 h. After drying, it was crushed to obtain an initial catalyst; In step S3, the Fe-Co / BFS-MgO catalyst is obtained by calcining at 550°C in an air atmosphere for 1 h.

[0052] Preparation Example 4 The catalyst was prepared by the same preparation method as in Preparation Example 3, except that in step S1, the blast furnace slag was crushed to obtain the first blast furnace slag, 20 g of the first blast furnace slag was weighed and mixed with 30 mL of nitric acid (concentration of 1 mol / L), soaked for 3 h, and then filtered and washed with deionized water until the pH value of the mixture reached 7. After that, the filter cake was placed in an oven at 120°C and dried for about 12 hours, and finally, calcined in air at 450°C for 1 hour. Finally, the Fe-Co / hn-BFS-MgO catalyst was prepared.

[0053] Preparation Example 5 A method for preparing a catalyst, comprising: S1. Provide initial blast furnace slag, wherein the blast furnace slag is crushed by high-speed shear crushing technology, and the first blast furnace slag is obtained by screening to obtain a 100 mesh or less, and 20g of the first blast furnace slag is weighed and mixed with 30 mL of nitrocitrate solution (concentration of 2 mol / L), soaked for 3 hours, and then filtered and washed with deionized water until the pH value of the mixture reaches 7. After that, the filter cake is placed in an oven at 120°C and dried for about 12 hours, and finally, it is roasted in air at 450°C for 1 hour to obtain initial blast furnace slag; S2. Enrich the catalytic metal and the modified metal in the initial blast furnace slag. Specifically, weigh 9.9 g of cobalt nitrate, 1.2 g of ammonium heptamolybdate and 3.2 g of magnesium nitrate, dissolve them in 53 mL of deionized water to form a mixed solution with a concentration of 1 mol / L, weigh 10 g of the initial blast furnace slag and mix it with the mixed solution, and stir it at high speed for 30 min at room temperature to form a suspension. Under continuous high-speed stirring, add a sodium carbonate solution with a concentration of 3 mol / L to the suspension, and control the dripping rate at 2 mL / min until the pH value of the mixed solution reaches the range of 9 to 11. Then, let it stand for 3 hours and wash it to neutrality with a centrifuge. Transfer the above precipitate to a 110 °C oven and dry it for 12 hours. After drying, crush it to obtain the initial catalyst; S3. The initial catalyst is calcined. Specifically, the initial catalyst is placed in a muffle furnace and calcined at 500° C. in an air atmosphere for 1 h to obtain a Co-Mo / ca-BFS-MgO catalyst (the citric acid modified blast furnace slag is recorded as ca-BFS).

[0054] Preparation Example 6 The catalyst was prepared by the same preparation method as in Preparation Example 5, except that in step S2, 9.9 g of cobalt nitrate, 1.2 g of ammonium heptamolybdate and 2.3 g of zinc nitrate were weighed and dissolved in 48 mL of deionized water to form a mixed solution with a concentration of 1 mol / L. Finally, the Co-Mo / ca-BFS-ZnO catalyst was prepared.

[0055] Preparation Example 7 A method for preparing a catalyst, comprising: S1. Weigh 7.2 g of ferric nitrate and 4.9 g of cobalt nitrate and dissolve them in 35 mL of deionized water to form a mixed solution with a concentration of 1 mol / L. Weigh 10 g of γ-Al2O3 and add it to the mixed solution. Stir at high speed for 6 h at room temperature, then heat to 80 °C and continue stirring until the water is completely evaporated to obtain a solid substance. Transfer the solid substance to a 100 °C oven and dry it for 12 h. After drying, crush it to obtain the initial catalyst; S2. Place the initial catalyst in a muffle furnace and calcine it at 600 °C in an air atmosphere for 0.5 h to obtain a Fe-Co / γ-Al2O3 catalyst.

[0056] Preparation Example 8 The catalyst was prepared by the same preparation method as in Preparation Example 7, except that γ-Al2O3 was replaced by MgO. Finally, a Fe-Co / MgO catalyst was prepared.

[0057] Preparation Example 9 A method for preparing a catalyst, comprising: S1. Weigh 7.2 g of ferric nitrate and 4.9 g of cobalt nitrate, and dissolve them in 35 mL of deionized water to form a mixed solution with a concentration of 1 mol / L. Weigh 10 g of CaO and add it to the mixed solution, and stir the obtained mixed solution at high speed for 30 minutes at room temperature to form a suspension. Under continuous high-speed stirring, add a 2 mol / L sodium hydroxide solution to the suspension at a rate of 1 mL / min until the pH value of the mixed solution reaches a range of 9 to 11. Then, let it stand for 3 hours and wash it to neutrality with a centrifuge. Transfer the precipitate to an 80 °C oven and dry it for 12 hours. After drying, crush it to obtain the initial catalyst; S2. The initial catalyst was placed in a muffle furnace and calcined at 550 °C in an air atmosphere for 1 h to finally prepare a Fe-Co / CaO catalyst.

[0058] Preparation Example 10 A method for preparing a catalyst, comprising: S1. Weigh 9.9 g of cobalt nitrate and 1.2 g of ammonium heptamolybdate, and dissolve them in 40 mL of deionized water to form a mixed solution with a concentration of 1 mol / L. Add 10 g of SiO2 to the mixed solution and stir at high speed for 30 min at room temperature to form a suspension. Under continuous high-speed stirring, add a 3 mol / L sodium carbonate solution to the suspension at a rate of 2 mL / min until the pH value of the mixed solution reaches a range of 9 to 11. Then, let it stand for 3 hours and wash it to neutrality with a centrifuge. Transfer the precipitate to a 110 °C oven and dry it for 12 hours. After drying, crush it to obtain the initial catalyst; S2. Place the above initial catalyst in a muffle furnace and calcine it at 500 °C in an air atmosphere for 1 h to obtain a Co-Mo / SiO2 catalyst.

[0059] Preparation Example 11 The catalyst was prepared by the same preparation method as in Preparation Example 10, except that SiO2 was replaced by γ-Al2O3, and finally a Co-Mo / γ--Al2O3 catalyst was prepared.

[0060] Preparation Example 12 The catalyst was prepared by the same preparation method as in Preparation Example 10, except that in step S1, 4.14 g of zirconium nitrate was added to the mixed solution. Finally, a Co-Mo / SiO2-ZrO2 catalyst was prepared.

[0061] The specific parameters of the components in the above preparation example are shown in Table 1, and the preparation parameters are shown in Table 2.

[0062] Table 1

[0063] Table 2

[0064] Example Example 1 A method for preparing carbon nanotubes, comprising: In a horizontal fixed bed reactor, 1 g of Fe-Co / BFS catalyst powder was evenly spread in a quartz boat. Subsequently, under the protection of 300 sccm nitrogen, it was heated to a set temperature of 680°C and 300 sccm of propylene gas was introduced. During this process, the flow rate of nitrogen remained constant. After 1 h of reaction, the supply of propylene gas was turned off and the mixture was naturally cooled to room temperature in a nitrogen atmosphere to obtain sample 1.

[0065] Example 2 The carbon nanotubes were prepared by the same preparation method as in Example 1, except that the temperature was set to 750° C. to obtain Sample 2.

[0066] Example 3 The carbon nanotubes were prepared by the same preparation method as in Example 1, except that 1 g of Fe-Co / hn-BFS catalyst was used, and finally Sample 3 was prepared.

[0067] Example 4 The carbon nanotubes were prepared by the same preparation method as in Example 1, except that 1 g of Fe-Co / BFS-MgO catalyst was used, and finally Sample 4 was prepared.

[0068] Example 5 Carbon nanotubes were prepared by the same preparation method as in Example 1, except that 1 g of Fe-Co / hn-BFS-MgO catalyst was used, and finally Sample 5 was prepared.

[0069] Example 6 Carbon nanotubes were prepared by the same preparation method as in Example 1, except that 1 g of Co-Mo / ca-BFS-MgO catalyst was used, and finally sample 6 was prepared.

[0070] Example 7 Carbon nanotubes were prepared by the same preparation method as in Example 1, except that 1 g of Co-Mo / ca-BFS-MgO catalyst was used and the temperature was heated to a set temperature of 750° C., and finally Sample 7 was prepared.

[0071] Example 8 Carbon nanotubes were prepared by the same preparation method as in Example 1, except that 1 g of Co-Mo / ca-BFS-ZnO catalyst was used, and finally sample 8 was prepared.

[0072] Comparative Example 1 Carbon nanotubes were prepared by the same preparation method as in Example 1, except that 1 g of Fe-Co / γ-Al2O3 catalyst was used, and finally sample 9 was prepared.

[0073] Comparative Example 2 Carbon nanotubes were prepared by the same preparation method as in Example 1, except that 1 g of Fe-Co / γ-Al2O3 catalyst was used and heated to a set temperature of 750°C, and finally sample 10 was prepared.

[0074] Comparative Example 3 The carbon nanotubes were prepared by the same preparation method as in Example 1, except that 1 g of Fe-Co / MgO catalyst was used, and finally sample 11 was prepared.

[0075] Comparative Example 4 The carbon nanotubes were prepared by the same preparation method as in Example 1, except that 1 g of Fe-Co / CaO catalyst was used, and finally sample 12 was prepared.

[0076] Comparative Example 5 Carbon nanotubes were prepared by the same preparation method as in Example 1, except that 1 g of Co-Mo / SiO2 catalyst was used, and finally sample 13 was prepared.

[0077] Comparative Example 6 Carbon nanotubes were prepared by the same preparation method as in Example 1, except that 1 g of Co-Mo / γ-Al2O3 catalyst was used, and finally sample 14 was prepared.

[0078] Comparative Example 7 Carbon nanotubes were prepared by the same preparation method as in Example 1, except that 1 g of Co-Mo / SiO2-ZrO2 catalyst was used, and finally sample 15 was prepared.

[0079] Comparative Example 8 Carbon nanotubes were prepared by the same preparation method as in Example 1, except that 1 g of Co-Mo / SiO2-ZrO2 catalyst was used and heated to a set temperature of 750°C, and finally sample 16 was prepared.

[0080] The specific preparation parameters of the embodiment are shown in Table 3 Table 3

[0081] Test Case The composition of the blast furnace slag in the preparation example was analyzed by X-ray fluorescence spectrometer (XRF), and the results are shown in Table 4. The specific surface area, pore volume and pore diameter of the blast furnace slag in the preparation example were tested, and the results are shown in Table 5. The carbon nanotubes prepared in the embodiment and the comparative example were tested by electronic scale to obtain the corresponding mass data of the carbon nanotubes, as shown in Table 6. The diameter and specific surface area of ​​the carbon nanotubes were measured and counted, and the statistical results are shown in Table 6. The microstructure of the carbon nanotubes in Example 1, Example 3, Comparative Example 1 and Comparative Example 3 was observed by FEI InspectF50 scanning electron microscope, and the microscopic morphology photos of the carbon nanotubes were obtained, corresponding to Figure 3 , Figure 4 , Figure 5 and Figure 6 As shown in the figure, it can be seen that the morphological characteristics of carbon nanotubes prepared by using blast furnace slag as a carrier and conventional carrier catalyst are consistent, both have multiple carbon nanotubes, the pore size is consistent, both show an oriented structure, and maintain microscopic morphological characteristics. It can be shown that the introduction of blast furnace slag carrier does not cause contamination of carbon nanotube growth, nor does it affect the morphological structure of the final carbon nanotube product.

[0082] Table 4

[0083] Table 5

[0084] It can be seen from Table 4 that by using blast furnace slag as a carrier, the content of key components meets the purity requirements and no additional impurities will be introduced to pollute the catalyst and the final product.

[0085] As can be seen from Table 5, in order to solve the problems of insufficient porosity, limited specific surface area and influence on loading and dispersion of active components when blast furnace slag is used as a catalyst carrier, strategies such as acid modification or inert component modification are adopted for blast furnace slag. These effective modification methods significantly optimize the performance of blast furnace slag as a catalyst carrier, significantly increase the specific surface area and pore volume, and provide a solid guarantee for the preparation of carbon nanotubes with better performance.

[0086] Table 6

[0087] It can be seen from the above experimental data that compared with the blast furnace slag multi-component composite carrier catalyst used in Examples 1 to 8, the carbon nanotubes prepared based on the catalyst of a single carrier in Comparative Examples 1 to 8 showed lower carbon yield, smaller specific surface area and thicker tube diameter. From the microstructural point of view, the carbon nanotubes prepared in Examples 1 and 3 showed an orderly bundle arrangement, and the tube diameter distribution was relatively uniform. In contrast, the carbon nanotubes prepared in Comparative Examples 1 and 3 were arranged in a disorderly manner, and the tube diameter was also thicker. These comparisons show that the multi-component composite carrier catalyst in the embodiment shows obvious advantages in improving catalytic activity and active metal dispersion ability compared with the single carrier catalyst in the comparative example.

[0088] Compared with Example 1 and Example 3, Examples 4 to 8 use metal oxide particles as modifiers to modify the blast furnace slag carrier. The results show that the blast furnace slag carrier catalyst modified by the modifier has a higher carbon nanotube yield and a larger specific surface area of ​​the carbon nanotubes.

[0089] Although the SiO2-ZrO2 two-component composite support catalyst in Comparative Example 7 has improved activity and metal dispersion ability compared to the single-support catalysts in Comparative Examples 1 to 6, it is still inferior to the performance of the multi-component composite support catalysts in Examples 1 to 8.

[0090] In addition, when comparing Example 1 with Example 2, and Example 6 with Example 7, the multi-component composite carrier catalyst proposed in the present application can still maintain high catalytic activity at a high temperature of 750°C, which is not reflected in the data of Comparative Examples 1 and 2, and Comparative Examples 7 and 8, the latter of which have significantly reduced activity under the same high temperature conditions. This result fully proves that the multi-component composite carrier catalyst developed in the present application not only has a wider active temperature window, but can also effectively resist temperature fluctuations during the production process, thereby ensuring the stability and reliability of the catalytic process.

[0091] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that the present invention includes but is not limited to the contents described in the drawings and the above specific embodiments. Any modification that does not deviate from the functional and structural principles of the present invention will be included in the scope of the claims.

Claims

1. A catalyst, characterized in that The catalyst is used for synthesizing carbon nanotubes, and the catalyst comprises: a body comprising a plurality of catalytic metal particles; A carrier, wherein the carrier comprises a plurality of carrier particles, wherein the carrier particles have a porous structure, the specific surface area of ​​the carrier particles is greater than the specific surface area of ​​the catalytic metal particles, the catalytic metal particles are supported by the carrier particles, and the material of the carrier particles comprises blast furnace slag; A modifier includes a plurality of metal oxide particles.

2. The catalyst according to claim 1, characterized in that A plurality of the metal oxide particles are distributed inside and / or on the surface of the carrier particles, and the plurality of the metal oxide particles are combined with the carrier particles.

3. The catalyst according to claim 2, characterized in that The modifier includes a basic metal oxide.

4. The catalyst according to claim 3, characterized in that The modifier includes at least one of magnesium oxide, zinc oxide, zirconium oxide and titanium oxide.

5. The catalyst according to claim 1, characterized in that In the catalyst, the modifier accounts for between 0.5% and 15% of the weight of the carrier.

6. The catalyst according to claim 1, characterized in that In the catalyst, the mass of the metal element in the main body is 10% to 30% of the weight of the carrier.

7. The catalyst according to any one of claims 1 to 6, characterized in that The metal element of the catalytic metal particles includes at least one of iron, cobalt and nickel.

8. A method for preparing a catalyst, characterized in that: The preparation method comprises: Providing initial blast furnace slag; Enriching catalytic metals and modifying metals in the initial blast furnace slag to obtain an initial catalyst; The initial catalyst is calcined to prepare the catalyst according to any one of claims 1 to 7, and the catalyst is used to synthesize carbon nanotubes.

9. The preparation method according to claim 8, characterized in that: The catalytic metal and the modified metal are enriched in the initial blast furnace slag to obtain the initial catalyst, comprising: Mixing a first metal salt, a second metal salt and water to form a mixed solution, wherein the metal in the first metal salt corresponds to the catalytic metal, and the metal in the second metal salt corresponds to the modified metal; The mixed solution is mixed with the initial blast furnace slag by an impregnation method or a co-precipitation method to obtain a first mixed solution; The first mixed liquid is dried and crushed to obtain the initial catalyst.

10. The preparation method according to claim 8, characterized in that: In the step of calcining the initial catalyst, the calcination temperature is between 300° C. and 700° C., and the calcination time is between 0.5 hour and 3 hours.

11. The preparation method according to any one of claims 8 to 10, characterized in that: Providing initial blast furnace slag includes: crushing the blast furnace slag to obtain first blast furnace slag; The first blast furnace slag is subjected to an acid modification treatment using an acid solution, wherein the acid solution corrodes the first blast furnace slag to form a surface microporous structure, thereby obtaining the initial blast furnace slag.

12. A method for preparing carbon nanotubes, characterized in that: The preparation method comprises: The catalyst is heated to between 680° C. and 800° C., and a carbon source gas is introduced to react to obtain initial carbon nanotubes, wherein the catalyst is the catalyst according to any one of claims 1 to 7; The initial carbon nanotubes are cooled to room temperature to obtain the carbon nanotubes.

13. A carbon nanotube, characterized in that: The carbon nanotubes are prepared by the preparation method described in claim 12.

Citation Information

Patent Citations

  • High-temperature methanation catalyst for producing natural gas through coal and preparation method of catalyst

    CN103706370A

  • Carbon nanotubes and method for manufacturing same

    CN103827027A

  • Preparation method and application method of blast furnace slag supported catalyst

    CN111558373A

  • Titanium-containing blast furnace slag loaded nano zero-valent iron material as well as preparation method and application thereof

    CN112844350A

  • Biomass tar reforming catalyst and preparation method thereof

    CN113600198A